Health problems in former elite female football players: Prevalence and risk factors - Prien, A.; Prinz, B.; Dvorak, J.; Junge, A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to assess the prevalence of health problems and associated risk factors in former elite female football players. A cross-sectional research design was employed, using an online questionnaire on personal characteristics and health complaints during/after the career. One hundred fifty-two (response rate: 62.0%) former first German league players answered the survey. Around 70% described their current health as good or very good. Over half (57.9%) reported knee problems during the last 4 weeks while exercising and a third (33.6%) during normal daily activities. The second most common location for complaints was the head (53.3%). Almost one quarter (23.7%) of players suffered from osteoarthritis (OA). Regression analysis showed that OA in knee/ankle and physical complaints (PC) in knee/ankle/head were significantly predicted by number and severity of previous injuries (P < 0.05). Further, increases in age, training volume, and level of play were associated with an increased likelihood of presenting with OA (P < 0.05), but not PC. In conclusion, a football career may lead to specific long-term health problems in elite female players. Prevention strategies should focus on knee, ankle, and head injuries. Future studies are needed to clinically assess the prevalence rates of OA and possible neurocognitive changes.